2015
DOI: 10.1080/00071668.2014.981503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fibre sources on performance, carcass characteristics and gastrointestinal tract development of growing Greylag geese

Abstract: 1. The effects of different fibre sources on the growth performance, carcass characteristics and gastrointestinal tract development were studied in growing Greylag geese (Anser anser). 2. Four experimental diets were formulated with corn (maize) straw silage (CSS), steam-exploded corn (maize) straw, steam-exploded wheat straw, and steam-exploded rice straw as fibre sources. A total of 224 male Greylag geese at 28 d of age were randomly assigned to one of the 4 experimental diets. 3. The birds fed on the CSS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
4
5
1
Order By: Relevance
“…Among the different genera, Bacteroides was the most abundant bacteria in goose caecum. Previous studies have shown that the microbial diversity in chicken caecum was mainly dominated by Bacteroides, which was consistent with our study1223. Bacteroides is thought to play a fundamental role in the breakdown of complex polysaccharides, starch and cellulose into simpler compounds27.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the different genera, Bacteroides was the most abundant bacteria in goose caecum. Previous studies have shown that the microbial diversity in chicken caecum was mainly dominated by Bacteroides, which was consistent with our study1223. Bacteroides is thought to play a fundamental role in the breakdown of complex polysaccharides, starch and cellulose into simpler compounds27.…”
Section: Discussionsupporting
confidence: 92%
“…Even if comparable proventriculus, small intestine and caecum, geese’s GIT has a bigger and more powerful gizzard. The powerful gizzards can generate greatest forces for breaking down the roughage with high fiber content, such as forage, corn straw silage, wheat straw and rice byproducts101112. Another pivotal reason is that geese have increasing effective caecum fermentation.…”
mentioning
confidence: 99%
“…Our results found that it was present in all probiotics-supplemented groups and the control group, ruling out the need for gut modulation of this bacteria. In addition, the microbial diversity of chicken caecum in the probiotics-supplemented group and control group was dominated by Bacteroides , consistent with a previous study 41, 48 . Bacteroides plays an important role in the breakdown of complex polysaccharides, starch and cellulose into simpler compunds 49 .…”
Section: Discussionsupporting
confidence: 91%
“…There were some studies that had similar LWG results as the current study (20,22,23). On the other hand, according to the results of the study that investigated the effects of different cellulose sources on the performance of geese, LWG was lower than (31.00, 31.30, 29.80, and 30.90 g) current study (24). The eviscerated carcass yields of the groups were 68.61%, 69.12%, 68.46%, respectively.…”
Section: Keskin Olmezsupporting
confidence: 70%